PENGGUNAAN BAHAN AJAR KIMIA BERORIENTASI KONSTRUKTIVISME PADA POKOK BAHASAN HIDROLISIS GARAM UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS XI IPA SMA NEGERI 1 KATEMAN KABUPATEN INDRAGIRI HILIR - Vivien Anjadi Suwito; Betty Holiwarni; Erviyenni ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Teaching materials chemistry constructivism oriented is the teaching materials have a structure of the content in the form of the introduction (the standard of competence, basic competence, indicators and the learning objectives), subject matter (description of the material ,table stuffing, pictures and illustrations) and student activities (matter ,conclusion ,sheet experiment) were prepared based approach constructivism to direct students to use the knowledge they had before to reach a conclusion of new knowledge as a whole. Through the calculation, the value of r is 0.07148513 thus obtained Kp rates at 7.15 % . This shows that the use of Instructional Materials Chemistry Constructivism Oriented On Salt Hydrolysis Improving Learning Enhancement Student Class XI IPA at SMAN 1 Kateman Indragiri Hilir at 7.15%. The use of teaching materials oriented constructivism influence on student learning enhancement. Constructivist-oriented teaching materials are intended to support students' active learning process that is useful to establish the knowledge and understanding that will affect student learning enhancement.Keywords: constructivism, learning material, knowledge